Redesain Pondok Pesantren Muhammadiyah Darul Arqam dengan Pendekatan Arsitektur Islam - Nahdatunnisa, Nahdatunnisa; Sari Taufiq, Elvina; Sabriadi, Sabriadi (Architectura : Journal of Architecture and Planning, 2025)
Muhammadiyah Darul Arqam Ponre Waru Islamic Boarding School in Wolo Sub-district, Kolaka Regency, needs a redesign to improve the quality of its space and function in accordance with the principles of Islamic architecture. This redesign aims to create a pesantren environment that is more comfortable, functional, and reflects Islamic values in the spatial layout and building design. The method used is descriptive-qualitative with literature study, site analysis, and direct observation. Islamic architectural principles are applied through harmonious spatial layout, qibla orientation, natural ventilation, and the use of materials that are appropriate to the environmental context. The design also considers aspects of sustainability and energy efficiency. The redesign is expected to optimally support the educational activities, worship, and life of students, as well as create an atmosphere that supports spiritual and social values in pesantren life.